Evolutionary Rates in Rapidly Diversifying Lineages (Zoological Archives: An International Journal, 2026)
Rapidly diversifying lineages -- adaptive radiations that generate disproportionate species richness over shortevolutionary timescales -- represent natural experiments in accelerated evolution, yet the molecular and morphologicalrate correlates of radiation tempo remain incompletely characterised across animal phyla. This study estimatedlineage-specific molecular evolutionary rates (substitution rates for 12 genes spanning synonymous, non-synonymous,and non-coding categories), morphological diversification rates (rate of disparity accumulation from geometricmorphometrics), and net diversification rates (speciation minus extinction; BAMM v2.5) for 28 animal adaptive radiationlineages across eight phyla (Vertebrata, Arthropoda, Mollusca, Echinodermata, and four invertebrate phyla) usingtime-calibrated phylogenies (24 published, 4 newly generated) encompassing 2,840 species. Molecular substitution rateswere significantly positively correlated with net diversification rates across lineages (r = +0.68, p < 0.001), withnon-synonymous rates (dN) showing the strongest correlation (r = +0.74) and synonymous rates (dS) the weakest (r =+0.28), consistent with positive selection at protein-coding loci contributing to accelerated diversification. Morphologicaldisparity accumulation rate was uncorrelated with molecular rate (r = +0.14, p = 0.48), indicating that molecularevolutionary acceleration does not necessarily translate into rapid morphological diversification. BAMM identified 18 rateshifts across the combined phylogeny, all associated with key ecological opportunity events: island colonisation (n = 8),prey base expansion (n = 6), and habitat transition (n = 4). Lineage-specific non-synonymous substitution rate was thestrongest single predictor of radiation net diversification rate (partial r = +0.68 after controlling for body size, generationtime, and ecological opportunity index). These results support the molecular evolutionary rate hypothesis for adaptiveradiation: elevated dN rates associated with positive selection on ecologically relevant traits facilitate rapid phenotypicdiversification and competitive exclusion enabling diversification into available niche space